Fuel requirements of spark ignition engines. (January 2018) - Kalghatgi, Gautam; Stone, Richard
This paper reviews the fundamental requirements of liquid hydrocarbon fuels for spark ignition engines, namely that the fuel should vaporise satisfactorily and burn in a controlled manner. The phenomenon of knock and the development of the octane scale are discussed. The variation in the pressure–time histories for different engines is discussed, together with the reason why this leads to different fuel requirements. The difference in the octane rating tests and the way in which engine downsizing exacerbates these differences in the pressure–time histories are discussed. The applicability of the research octane number and the motor octane number to modern engines is reviewed, together with the phenomena of low-speed pre-ignition and superknock. The effects of the hydrocarbon fuel distillation characteristics on the driveability and the emissions are reviewed and discussed with respect to the historical context and the current legislative requirements. Brief mention is made of other fuel requirements such as the density, the gum content and the aromatic content.